Genome-Wide Diversity of MADS-Box Genes in Bread Wheat is Associated with its Rapid Global Adaptability - Raza, Qasim; Riaz, Awais; Atif, Rana Muhammad; Hussain, Babar; Rana, Iqrar Ahmad; Ali, Zulfiqar; Budak, Hikmet; Alaraidh, Ibrahim A. (Frontiers in Genetics, 2022)
MADS-box gene family members play multifarious roles in regulating the growth and development of crop plants and hold enormous promise for bolstering grain yield potential under changing global environments. Bread wheat (Triticum aestivum L.) is a key stable food crop around the globe. Until now, the available information concerning MADS-box genes in the wheat genome has been insufficient. Here, a comprehensive genome-wide analysis identified 300 high confidence MADS-box genes from the publicly available reference genome of wheat. Comparative phylogenetic analyses with Arabidopsis and rice MADS-box genes classified the wheat genes into 16 distinct subfamilies. Gene duplications were mainly identified in subfamilies containing unbalanced homeologs, pointing towards a potential mechanism for gene family expansion. Moreover, a more rapid evolution was inferred for M-type genes, as compared with MIKC-type genes, indicating their significance in understanding the evolutionary history of the wheat genome. We speculate that subfamily-specific distal telomeric duplications in unbalanced homeologs facilitate the rapid adaptation of wheat to changing environments. Furthermore, our in-silico expression data strongly proposed MADS-box genes as active guardians of plants against pathogen insurgency and harsh environmental conditions. In conclusion, we provide an entire complement of MADS-box genes identified in the wheat genome that could accelerate functional genomics efforts and possibly facilitate bridging gaps between genotype-to-phenotype relationships through fine-tuning of agronomically important traits.